Tourism development in Łódź in 2000-2014: directions and character of change - Kowalczyk-Anioł, Joanna (Turyzm/Tourism, 2015)
The primary aim of the article is to present the scope and character of tourism in Łódź, between 2000 and 2014. The author will show both the overall changes in numbers of registered tourists during those 15 years, its distribution within the city in the last year, and the number and specificity of foreign arrivals (non-residents). Based on surveys in 2009-12, the author will discuss the structure of tourism in Łódź, taking into consideration one-day visitors and tourists, tourism consumption and distribution within the city space.